2023
DOI: 10.1038/s41598-023-32435-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo full length transcriptome analysis of a naturally caffeine-free tea plant reveals specificity in secondary metabolic regulation

Abstract: Tea plants are crops with economic, health and cultural value. Catechin, caffeine and theanine are the main secondary metabolites of taste. In the process of germplasm collection, we found a resource in the Sandu Aquatic Autonomous County of Guizhou (SDT) that possessed significantly different characteristic metabolites compared with the cultivar ‘Qiancha 1’. SDT is rich in theobromine and theophylline, possesses low levels of (−)-epicatechin-3-gallate, (−)-epigallocatechin-3-gallate, and theanine content, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For example, Yang et al identified 121,955 unigenes in Panax notoginseng [ 59 ]. Mi et al identified 78,809 unique transcripts in Camellia sinensis , with 65,264 being complete coding sequences [ 60 ]. Based on the ONT and Illumina sequencing technologies, a total of 107,977 unigenes were identified and successfully annotated in seven public databases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al identified 121,955 unigenes in Panax notoginseng [ 59 ]. Mi et al identified 78,809 unique transcripts in Camellia sinensis , with 65,264 being complete coding sequences [ 60 ]. Based on the ONT and Illumina sequencing technologies, a total of 107,977 unigenes were identified and successfully annotated in seven public databases.…”
Section: Discussionmentioning
confidence: 99%